“Falsa la historia que nos enseñaron”. Argumentos visuales, sensibilización y revisión de la historia desde el peronismo revolucionario (Argentina, 1966/1976) - Moira Cristiá (Centre de Recherches sur les Mondes Américains, 2011)
This presentation aims to analyze how revolutionary Peronism of the sixties and seventies contests the argentinean "official history" and proposes a new interpretation of the national past. By studying their conception of history, this paper focuses on how image is employed in order to diffuse a new interpretation of reality. The hypothesis is that historical milestones are used as sensitive arguments to discuss the present and to legitimize a political alternative project. The promotion of the new version of history is based on provoking feelings through visual material and exalting other history protagonists. By evoking some graphic and film examples, this paper demonstrates how image is supposed to raise public awareness and as arguments for politics.